Recent advances in drug delivery systems for targeting cancer stem cells - Hongxia Duan; Yanhong Liu; Zhonggao Gao; Wei Huang (Elsevier, 2021)
Cancer stem cells (CSCs) are a subpopulation of cancer cells with functions similar to those of normal stem cells. Although few in number, they are capable of self-renewal, unlimited proliferation, and multi-directional differentiation potential. In addition, CSCs have the ability to escape immune surveillance. Thus, they play an important role in the occurrence and development of tumors, and they are closely related to tumor invasion, metastasis, drug resistance, and recurrence after treatment. Therefore, specific targeting of CSCs may improve the efficiency of cancer therapy. A series of corresponding promising therapeutic strategies based on CSC targeting, such as the targeting of CSC niche, CSC signaling pathways, and CSC mitochondria, are currently under development. Given the rapid progression in this field and nanotechnology, drug delivery systems (DDSs) for CSC targeting are increasingly being developed. In this review, we summarize the advances in CSC-targeted DDSs. Furthermore, we highlight the latest developmental trends through the main line of CSC occurrence and development process; some considerations about the rationale, advantages, and limitations of different DDSs for CSC-targeted therapies were discussed.